Dupuytren’s Contracture With Rare Bilateral Thumb and Little Finger Involvement Demonstrated by Ultrasound Elastography - Aslıhan ULUSOY; Canan TIKIZ; Şebnem ÖRGÜÇ (Archives of Rheumatology, 2015)
Dupuytren’s contracture is a disease that affects the functionality of the hand and causes contractures leading to progressive fibrosis of the palmar fascia. Dupuytren’s contracture usually affects the fourth and fifth digits, but thumb involvement is rare. In this article, we presented a rare case of Dupuytren’s contracture with bilateral thumb and fifth digit involvement in a 77-year-old male patient who was assessed by ultrasound elastography and gained range of motion after rehabilitation.